Prospects for improving evaluation of live tularemia vaccine quality - I. V. Kasina; S. A. Alekseeva; Z. E. Berdnikova; T. I. Nemirovskaya; A. S. Alekhina (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article presents prospects for improving the evaluation of live tularemia vaccine (hereinafter - tularemia vaccine) quality in terms of the following parameters: «Identification», «Specific activity (the number of living microbial cells)» and the «Absence of extraneous microorganisms and fungi». The authors investigated the possibility of improving evaluation of tularemia vaccine quality as regards the «Identification» parameter by using a commercial diagnostic test kit - immunochromatographic test system for express detection and identification of tularemia agent («F. tularensis ICA test system»). In order to optimize and improve the evaluation of tularemia vaccine quality as regards «Specific activity (the number of living microbial cells)» parameter it is recommended to use a ready-to-use growth medium for cultivation and isolation of tularemia microbe - as an additional culture medium for determination of the number of living microbial cells. It is proposed to improve the methodology of tularemia vaccine quality evaluation as regards the «Absence of foreign microorganisms and fungi» parameter by eliminating the stage of subculturing material in thioglycollate medium for 5-7 days, which is reasonable from economic and practical points of view and also reduces the risk of false positive results.